SOCIALIZATION OF CORRECT HANDWASHING STEPS TO CREATE A HEALTHY STUDENTS AT DENANYAR, JOMBANG, INDONESIA - Hernaningsih, Yetti; Aulia, Fauqa Arinil; Rini, Rini; Wardhani, Puspa (Universitas Airlangga, 2023)
Elementary school students in Indonesia generally do not know the proper and correct steps for washing hands according to the World Health Organization (WHO), which is indicated by the high rate of spread of hand-borne diseases, including diarrhea. Diarrhea is an endemic disease in Jombang Regency with the incidence rate increasing in 2019 compared to 2018. Teaching Staff of the Department of Clinical Pathology, Faculty of Medicine, UNAIR, carry out community service activities with the aim of providing education on how to wash hands properly and correctly for Madrasah Ibtidaiyah students (MI) Mambaul Maarif Denanyar Jombang. The method of socializing the correct hand washing steps is carried out in two stages, namely education and evaluation. The education carried out is an explanation of the correct steps for washing hands according to WHO, what germs are found on human hands, what diseases can be transmitted through hands, and when we should wash our hands. Evaluation is carried out by culturing germs from the surface of the hands at two times, namely before and after washing hands. The data obtained is the difference in bacterial culture results in specimens before and after washing hands. The growth of bacteria before hand washing showed more colonies compared to after hand washing.